2009
DOI: 10.1152/ajpcell.00617.2008
|View full text |Cite
|
Sign up to set email alerts
|

Preadipocyte apoptosis is prevented by macrophage-conditioned medium in a PDGF-dependent manner

Abstract: Molgat AS, Gagnon A, Sorisky A. Preadipocyte apoptosis is prevented by macrophage-conditioned medium in a PDGF-dependent manner. Am J Physiol Cell Physiol 296: C757-C765, 2009. First published February 18, 2009 doi:10.1152/ajpcell.00617.2008.-Obesity is associated with macrophage accumulation and inflammation in adipose tissue. Macrophage-secreted factors have been reported to inhibit the differentiation of preadipocytes into adipocytes and to modulate adipogenic extracellular matrix gene expression. To enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…This resistance to apoptosis stimuli has also been shown for primary human preadipocytes and adipocytes (Fischer-Posovszky et al, 2004). We suggest that 3T3-L1 cells benefit from macrophagesecreted factors such as PDGF (Molgat et al, 2009) which are known to rescue cells from apoptosis. In M a n u s c r i p t 15 addition, it has been shown that macrophage media stimulate Akt phosphorylation in 3T3-L1 cells (Molgat et al, 2011), further supporting the differences between murine and human cells.…”
Section: Discussionsupporting
confidence: 72%
“…This resistance to apoptosis stimuli has also been shown for primary human preadipocytes and adipocytes (Fischer-Posovszky et al, 2004). We suggest that 3T3-L1 cells benefit from macrophagesecreted factors such as PDGF (Molgat et al, 2009) which are known to rescue cells from apoptosis. In M a n u s c r i p t 15 addition, it has been shown that macrophage media stimulate Akt phosphorylation in 3T3-L1 cells (Molgat et al, 2011), further supporting the differences between murine and human cells.…”
Section: Discussionsupporting
confidence: 72%
“…We have studied another cell fate, survival, and have previously reported that MacCM from J774A.1 macrophages protects 3T3-L1 preadipocytes from apoptosis in a PDGF-dependent manner, measured by cell enumeration, Hoechst staining, and annexin V detection by flow cytometry (Molgat et al 2009. Here, we report that pro-inflammatory macrophage activation reduces the pro-survival activity of J774A.…”
Section: Discussionmentioning
confidence: 63%
“…We previously reported that J774A.1-MacCM, in a PDGFdependent manner, inhibits apoptosis of serum-deprived 3T3-L1 preadipocytes, and this was documented by cell enumeration, Hoechst staining, and annexin V detection by flow cytometry (Molgat et al 2009. We have now investigated, for the first time, the effect of pro-inflammatory macrophage activation, induced by LPS treatment, on the preadipocyte survival activity of MacCM.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations